Change in agricultural land use constrains adaptation of national wildlife refuges to climate change. (22nd May 2014) - HAMILTON, CHRISTOPHER M.; THOGMARTIN, WAYNE E.; RADELOFF, VOLKER C.; PLANTINGA, ANDREW J.; HEGLUND, PATRICIA J.; MARTINUZZI, SEBASTIAN; PIDGEON, ANNA M.
SUMMARY: Land-use change around protected areas limits their ability to conserve biodiversity by altering ecological processes such as natural hydrologic and disturbance regimes, facilitating species invasions, and interfering with dispersal of organisms. This paper informs USA National Wildlife Refuge System conservation planning by predicting future land-use change on lands within 25 km distance of 461 refuges in the USA using an econometric model. The model contained two differing policy scenarios, namely a 'business-as-usual' scenario and a 'pro-agriculture' scenario. Regardless of scenario, by 2051, forest cover and urban land use were predicted to increase around refuges, while the extent of range and pasture was predicted to decrease; cropland use decreased under the business-as-usual scenario, but increased under the pro-agriculture scenario. Increasing agricultural land value under the pro-agriculture scenario slowed an expected increase in forest around refuges, and doubled the rate of range and pasture loss. Intensity of land-use change on lands surrounding refuges differed by regions. Regional differences among scenarios revealed that an understanding of regional and local land-use dynamics and management options was an essential requirement to effectively manage these conserved lands. Such knowledge is particularly important given the predicted need to adapt to a changing global climate.